The usage of drugs with cerebrovascular activity in mice with reduced attention level - N. A. Sukhorukova; R. M. Salimov; G. I. Kovalev (LLC "Publisher OKI", 2022)
The effect of picamilon (50 mg/kg/day), tropoxin (10 mg/kg/day) and LK-933 (9,3 mg/kg/day) on the behavior of CD-1 mice phenotypes with different attention stability in the "closed enriched cross maze" test after 6 days of intraperitoneal administration was studied. It was shown for the first time that in mice with native attention deficit drugs with nootropic and cerebrovascular activity improved attention. Observed effect was combined with changings of exploratory behavior parameters, motor activity and anxiety in both mice subpopulations. Obtained results allow to make an assumption about further experimental study of drugs with cerebrovascular properties in the attention deficit disorder model proposed by the authors.